2016
DOI: 10.15640/jthm.v4n2a5
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption and Use of Renewable Energy Sources in Hotels: A Case Study in Crete, Greece

Abstract: The energy analysis of five summer operating hotels in Crete, Greece was implemented and their average annual energy consumption has been estimated at 149 KWh/m 2 and 19.4 KWh/p.n.s. Their average annual CO2 emissions due to energy use have also been estimated at 12.1 kg CO2/p.n.s.. Hotels in Crete utilize various renewable energy technologies with solar thermal energy being the most widely used. Apart from solar thermal energy, solar cooling, passive solar, solar-PV, solid biomass burning and low enthalpy geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Huang et al [43] confirmed that hotels are considered as the most energy-consuming type of building due to their multi-usage functions and continuous operation. According to their findings, most hotels' energy use falls in the range of 200-400 KWh/m 2 yr, with the average energy use in the range 305-330 KWh/m 2 yr [44,45]. As a result, decreasing the energy consumption across the hotel often leads to lower operational cost and fewer environmental impacts.…”
Section: Food Wastes Of Hospitality Sectormentioning
confidence: 99%
“…Huang et al [43] confirmed that hotels are considered as the most energy-consuming type of building due to their multi-usage functions and continuous operation. According to their findings, most hotels' energy use falls in the range of 200-400 KWh/m 2 yr, with the average energy use in the range 305-330 KWh/m 2 yr [44,45]. As a result, decreasing the energy consumption across the hotel often leads to lower operational cost and fewer environmental impacts.…”
Section: Food Wastes Of Hospitality Sectormentioning
confidence: 99%
“…In the case of CE energy measurements, Vourdaubas [19] (2016) found that hospitality in Greece used renewable energy sources including thermal, geothermal and biomass generated energy. Girard and Nocca [3] (2017) explained that some CE measurements taken in Italian hotels used natural gas, electric buses and zero km menus.…”
Section: Circular Economy In the Hospitality Industrymentioning
confidence: 99%
“…The hotel building has many areas with different facilities and diverse variability in the room that guests expect. This leads to a different energy consumption compared to other buildings [2]. Buildings account for the majority of energy consumption worldwide [3][4][5].…”
Section: Introductionmentioning
confidence: 99%